The state of dyslipidemia after laparoscopic sleeve gastrectomy - Hussein, Ahmed Mahmoud (International Surgery Journal, 2018)
Background: Obesity and dyslipidemia have a strong relation to the development of cardiovascular diseases. Bariatric surgery is directed towards the loss of patients weight and resolution of comorbidities as hyperlipidemia. Laparoscopic sleeve gastrectomy, a feasible restrictive procedure, is one the most popular and successful operations for achieving this purpose. The aim of present study was to evaluate the effect of laparoscopic sleeve gastrectomy on the lipid profile, comparing preoperative with postoperative results 12 months after surgery. Methods: This study included fifty morbidly obese cases that underwent laparoscopic sleeve gastrectomy (LSG). Preoperative and postoperative BMI and lipid parameters were documented and analysed at 12 months postoperatively. Results: The mean age of the studied group ±SD was 32.7±9.2 years, female predominance was found. BMI improved significantly after the LSG procedure with a mean±SD of 32.2±4 kg/m2. A significant improvement of dyslipidemia was found with a p-value (<0.001) regarding the mean level±SD of total cholesterol (TC) (180.5±25mg/dl), triglycerides (TG) (127.2±14.7mg/dl), low density lipoprotein (LDL) (94.2±14.5mg/dl) and high density lipoprotein (HDL) (48.4±5.6 mg/dl). Conclusions: Laparoscopic sleeve gastrectomy is a feasible and successful operation in reducing the body weight and subsequently improving the dyslipidemia of the morbid obese individuals.